The interaction between gut microbiota and host DNA methylation in the pathogenesis and therapy of inflammatory bowel disease - Jin, Qing; Li, Xiang; Liu, Zhonggui; Qi, Tingting; Xiao, Dewang; Yang, Wentai (Frontiers in Microbiology, 2025)
Inflammatory bowel disease (IBD) represents a multifaceted, chronic inflammatory disorder of the gastrointestinal tract, with its pathogenesis modulated by a confluence of genetic, environmental, and immunological factors. Recent advancements have underscored the significance of the interaction network between gut microbiota and host epigenetic regulation, particularly via DNA methylation, as a pivotal area of investigation in elucidating the mechanisms underlying IBD. The gut microbiota exerts influence on host gene expression through its metabolic byproducts, thereby modulating immune responses and intestinal barrier integrity, while changes in host DNA methylation status both reflect and mediate this complex interaction. This review delineates the molecular mechanisms that regulate the interplay between gut microbiota and host DNA methylation, examines the impact of environmental factors on the onset and progression of IBD through microbiota-epigenetic pathways, and highlights recent multi-omics research findings and their potential applications in precision medicine. The objective is to furnish a theoretical framework and research trajectory for deciphering the molecular underpinnings of IBD and fostering the development of innovative therapeutic strategies.